PARADIGMA INTEGRASI ILMU DALAM ARSITEKTUR PENGEMBANGAN PERGURUAN TINGGI ISLAM DI ERA TRANSFORMASI - Suyoko; Ngainun Naim; Akhyak (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
Islamic higher education in the era of digital transformation faces significant challenges in formulating relevant and adaptive models of knowledge integration. With technological disruption and globalization, Islamic higher education institutions need to develop educational systems that not only uphold Islamic values ​​but also accommodate the development of modern science. This study aims to explore various models of knowledge integration in the development of Islamic higher education institutions, focusing on four Islamic universities in Indonesia: UIN Jakarta, UIN Yogyakarta, UIN Malang, and UIN Surabaya. The method used in this study is a Systematic Literature Review (SLR), which analyzes the latest scientific articles from 2020 to 2025 regarding the integration of knowledge in Islamic higher education. The results show that each university develops a unique model, despite having the same goal of uniting religious and general knowledge. UIN Jakarta uses a dialogical approach, UIN Yogyakarta develops an interdisciplinary interconnection model, UIN Malang utilizes the metaphor of the "tree of knowledge" to describe the relationship between religious and general knowledge, while UIN Surabaya applies the Twin Towers model that harmonizes both realms of knowledge. This study concludes that the integration of knowledge in Islamic higher education needs to accommodate the development of the times without losing its Islamic substance, and each model implemented has its own unique way of connecting religious and general knowledge